2019
DOI: 10.1097/dss.0000000000001895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preservation Solutions on the Trichogenicity of Hair Micrografts Ascertained by Dermal Papilla Gene Expression

Abstract: BACKGROUND Appropriate storage of human hair follicle (HF) grafts during follicular unit excision (FUE) is crucial toward successful hair shaft implantation. Several commercial storage solutions are currently used to ensure ex vivo maintenance of follicular grafts viability and trichogenicity. However, quantitative experimental evidence demonstrating molecular changes in HF cells associated with the usage of different storage solutions is largely missing. OBJECTIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, indirect application of NTAPP such as plasma-treated medium can be a feasible approach to overcome the penetration issue 43 . Notably, we have shown the maintenance of hair-inductive ability verified by upregulated ALPL and VCAN after NTAPP exposure on isolated fresh hHFs, which implies NTAPP can be applied on a novel device enhancing viability or survival rate of grafts during hair transplantation 44 .…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, indirect application of NTAPP such as plasma-treated medium can be a feasible approach to overcome the penetration issue 43 . Notably, we have shown the maintenance of hair-inductive ability verified by upregulated ALPL and VCAN after NTAPP exposure on isolated fresh hHFs, which implies NTAPP can be applied on a novel device enhancing viability or survival rate of grafts during hair transplantation 44 .…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have investigated effects of different preservation conditions on the protection of hair grafts (overview in See Supplemental Digital Content 1, Table S1, http://links.lww.com/DSS/B257). The chilled preservation temperature is the primary determinant of graft viability, 11,[19][20][21] which slows metabolism to avoid ischemic injury. In addition, the authors have previously explored the optimum temperature for isolated hair grafts, and results showed 4°C kept the best survival rate compared with room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that saline preservation significantly reduces expression levels of trichogenic genes (including HEY1), and induces inflammatory signaling (including JAK-STAT), which potentially triggers an anagen-to-catagen transition. 11,12 Apoptosis of metabolically active stem cells promotes shock loss after HT. 11 In this article, live/dead staining confirmed RS grafts had more apoptotic cells centered at the hair bulb than those in HTK-AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations